Предмет: Алгебра,
автор: justrenata1
x^2-2x-3=0 (теорема Виета)
Ответы
Автор ответа:
0
по теореме Виетта:
х первое + х второе = -В
х первое * х второе = С
в нашем случае:
х первое + х второе = 2
х первое * х второе = -3
методом подстановки получаем х первое = 3, х второе = -1
х первое + х второе = -В
х первое * х второе = С
в нашем случае:
х первое + х второе = 2
х первое * х второе = -3
методом подстановки получаем х первое = 3, х второе = -1
Похожие вопросы
Предмет: География,
автор: shaforostova56
Предмет: Математика,
автор: irinagavazina31
Предмет: Русский язык,
автор: milenapoxosyan8
Предмет: Математика,
автор: Александрочкачка